Makna Budaya dan Nilai Pendidikan Karakter dalam Syair Ikan Terubuk - Supriyadi, Supriyadi; Hidayat, Rian; Tawaqal, Ridwan (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to describe the characters' cultural meaning and educational values ​​in the poem Ikan Terubuk. It explains that people's moral education results from the refinement of the values ​​instilled since ancient times. Besides, it could also be useful for developing regional literature and enriching teaching materials for teachers of Indonesian language and literature and the learning of local culture, especially in the Riau. Thus, the poem Ikan Terubuk can be known and understood by the next generation so that local wisdom characteristics remain preserved and well maintained by the community. This type of research was qualitative with descriptive methods. The data collection technique used was the note-taking technique. The subject of this research was the poem Ikan Terubuk. This research aimed to focus on stylistic elements, cultural meanings, and educational values ​​of character in the poem Ikan Terubuk. Data analysis through steps: data reduction, data presentation, and inference. The reliability of intra-rater and inter-rater obtained the validity of data. After clarifying the 10 data, it is reflected in the poetry of Ikan Terubuk, which is still developing contextually and has shifted functionally as a magical power in a ritual ceremony in Riau. The religious, nationalist, independent, cooperative, and integrity values showed moral education in this poem. The Islamic values became the dominant value in the poem Ikan Terubuk because it has relevance to the ethnic Malay majority Bengkalis as a devout Muslim.